Development of an Information System for eTax Return Reporting PPh 21 Employees at PT. FBR Mitra Sejati - Hasibuan, Maimunah Permata Hati; Prasetio, Primadi (Internet of Things and Artificial Intelligence Journal, 2024)
This research aims to develop an information system that supports collecting Income Tax (PPh) for employees in a tax consulting company. This research analyzes the suitability of the tax collection procedures applied by the company and the applicable tax provisions. The method used in this research is descriptive analysis based on data obtained through interviews, observations, and literature review. The results show that the principle of income tax collection in tax consulting companies is in line with the general tax withholding method, with estimated net income as the basis for calculation. The tax rate variations applied include the provisions in Article 17 of the Income Tax Law and related government regulations. The information system developed aims to improve efficiency and accuracy in the reporting of Income Tax Return 21 and support better tax compliance.